Processless offset printing plates - Mahović Poljaček, Sanja; Cigula, Tomislav; Hoffmann-Walbeck, Thomas; Tomašegović, Tamara; Riegel, Sebastian (Journal of Graphic Engineering and Design, 2023)
With the implementation of platesetters in the offset printing plate making process, imaging of the printing plate became more stable and ensured increase of the printing plate quality. But as the chemical processing of the printing plates still highly influences the plate making process and the graphic reproduction workflow, development of printing plates that do not require chemical processing for offset printing technique has been one of the top interests in graphic technology in the last few years. The main reason for that came from the user experience, where majority of the problems with plate making process could be connected with the chemical processing of the printing plate. Furthermore, increased environmental standards lead to reducing of the chemicals used in the industrial processes. Considering these facts, different types of offset printing plates have been introduced to the market today. This paper presents some of the processless printing plates.